(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
Blake’s Fleabane, Erigeron blakei Cabrera, is reported for the first time in the department of Puy-de-Dôme (Auvergne, France), in different places of the metropolis of Clermont-Ferrand.